Pendampingan dan Pelatihan Rebranding Produk Susu Sapi Perah untuk Meningkatkan Citra dan Penjualan pada UMKM Lokal - Saifulloh Saifulloh; Alim Citra Aria Bima; Ibnu Adityasa; Miftachul Huda (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
Micro, Small, and Medium Enterprises (UMKM) play a crucial role in driving local economic growth, particularly in the food and beverage sector. However, many UMKM, such as Cipta Rasa Mulya, still face significant challenges in adopting modern marketing approaches to expand their reach and enhance their competitiveness. This community service program focuses on addressing two major issues: the lack of effective digital marketing utilization and the weak brand identity—especially in packaging design—of the dairy products produced by the UMKM. Through a structured and intensive training program, this initiative aims to provide UMKM actors with comprehensive knowledge and practical skills in rebranding and digital marketing. The activities include workshops on digital branding strategies, hands-on mentoring sessions for social media management, product photography, and brand storytelling, as well as ongoing evaluations to monitor progress and implementation. The expected outcomes of this program are multifaceted, including improved brand awareness among consumers, more attractive and informative packaging, increased product variety, and broader market reach through the use of digital platforms such as Instagram, TikTok, and e-commerce channels. By enhancing the UMKM’s ability to present their products professionally and utilize social media for marketing purposes, this program supports the development of more competitive and sustainable business practices. In the long term, it is anticipated that such interventions will not only increase the visibility of Cipta Rasa Mulya’s dairy products but also strengthen their position in both local and national markets. Ultimately, this initiative highlights the importance of combining technological adaptation with creative branding in empowering UMKM and stimulating inclusive economic growth.